Biomechanical Effects of Different Load Cases with an Implant-Supported Full Bridge on Four Implants in an Edentulous Mandible: A Three-Dimensional Finite Element Analysis (3D-FEA) - Árpád László Szabó; Danica Matusovits; Haydar Slyteen; Éva Ilona Lakatos; Zoltán Baráth (MDPI AG, 2023)
The long-term success and predictability of implant-supported restorations largely depends on the biomechanical forces (stresses) acting on implants and the surrounding alveolar bone in the mandible. The aim of our study was to investigate the biomechanical behavior of an edentulous mandible with an implant-supported full bridge on four implants under simulated masticatory forces, in the context of different loading schemes, using a three-dimensional finite element analysis (3D-FEA). A patient-specific 3D finite element model was constructed using pre- and post-implantation computer tomography (CT) images of a patient undergoing implant treatment. Simplified masticatory forces set at 300 N were exerted vertically on the denture in four different simulated load cases (LC1-LC4). Two sets of simulations for different implants and denture materials (S1: titanium and titanium; S2: titanium and cobalt-chromium, respectively) were made. Stress outputs were taken as maximum (Pmax) and minimum principal stress (Pmin) and equivalent stress (Peqv) values. The highest peak Pmax values were observed for LC2 (where the modelled masticatory force excluded the cantilevers of the denture extending behind the terminal implants), both regarding the cortical bone (S1 Pmax: 89.57 MPa, S2 Pmax: 102.98 MPa) and trabecular bone (S1 Pmax: 3.03 MPa, S2 Pmax: 2.62 MPa). Overall, LC1-where masticatory forces covered the entire mesio−distal surface of the denture, including the cantilever-was the most advantageous. Peak Pmax values in the cortical bone and the trabecular bone were 14.97-15.87% and 87.96-94.54% higher in the case of S2, respectively. To ensure the long-term maintenance and longevity of treatment for implant-supported restorations in the mandible, efforts to establish the stresses of the surrounding bone in the physiological range, with the most even stress distribution possible, have paramount importance.